DECENTRALIZATION IN PRACTICE: MANAGEMENT OF CULTURAL INSTITUTIONS BY POLISH LOCAL GOVERNMENT - Ksenicz, I. (Pressing Problems of Public Administration, 2019)
According to experts of Polish National Centre for Culture, local government plays the main role in Polish cultural policy. In 2014, 81 % of Poland’s public expenditures on culture came from the local government. In the European Union member states there are four models of organization and financing culture: 1. central organization and budget financing (France), 2. central organization and fund financing (Scandinavia, Netherlands), 3. sub-central organization and budget financing (United Kingdom), 4. local organization and decentralized financing (Germany). Dorota Jurkiewicz-Eckert from Warsaw University named Polish cultural policy “post-transitional”. It allows only chosen state entities and programs to work stably, at the same time transmitting majority of tasks in the area of culture to the local government. Culture is an important element of social life. In Polish law, it is highlighted in the constitution of the Republic of Poland from April 2, 1997. In terms of organizing the cultural activity, the law on organizing and conducting cultural activity from October 25, 1991, is of great importance. This legal act states that conducting cultural activity is an own task of local government. Laws on system of Polish territorial self-government (law on local self-government from March 8, 1990; law on district self-government from June 5, 1998; law on regional self-government from June 5, 1998) confirm prior regulations. Law on public benefit activity and volunteering from April 24, 2003, is crucial for non-government sector, as it introduces financial mechanisms of cooperation between public administration, including local government, and NGO’s. Public benefit activity concerns culture as well. According to reports of “Wspуlnota”(“Community”) journal and Polish Supreme Audit Office, level of expenditures for culture in local government budgets is around 3–4 %. In the period 2000–2013 those expenditures increased from 2,5 to 6,7 billion PLN. Libraries comprise 60 % of all cultural institutions run by local government, community centers – 26,8 %. The main barrier of development for local cultural entities in Poland is insufficient financing.